Implementation of vegetable consumption education in the Elementary School curriculum: A case study G7KAIH program - Deris Aprianty; Drajat Martianto; Ali Khomsan; Yayuk Farida Baliwati (AcTion: Aceh Nutrition Journal, 2026)
Low vegetable consumption among elementary school students in Indonesia persists despite the national policy implemented through the “Gerakan 7 Kebiasaan Anak Indonesia Hebat (G7KAIH).” Previous studies have primarily examined nutritional intake outcomes, whereas limited attention has been paid to how vegetable consumption education policies are translated into classroom practice. This study aimed to analyze the integration of vegetable consumption education into the elementary school curriculum through G7KAIH and identify the implementation factors affecting learning practices and vegetable consumption habituation. A descriptive qualitative case study was conducted at a public elementary school in Tasikmalaya City, Indonesia, from October to December 2025. Data were collected through in-depth interviews and focus group discussions with education officials, school principals, teachers, and a nutritionist. Plate waste was identified through student consumption monitoring and simple recording of food waste at school. Data were analyzed thematically using Edward III’s policy-implementation framework. The findings indicate that policy communication was formally conducted but was not supported by operational guidelines, teacher capacity, or a clear implementation structure. Consequently, vegetable consumption education remained largely administrative and was not fully operationalized in daily learning processes. In conclusion, plate waste may serve as a behavioral indicator reflecting the translation of educational policy messages into classroom practice and students’ eating behaviors.